Nickel electrodeposition using deep eutetectic solvent-based electrolyte - Dela Peña, Eden May B. (2023)
While nickel (Ni) electroplating has been successfully performed using ionic liquids in the past, few have reported on the trench-filling characteristics of this process useful for electroforming Ni. This study aimed to deposit and characterize the electrodeposited nickel using an enthaline-based ૦-plating bath with and without enthlenediamine (en). The conductivity of the plating bath was improved, whereas viscosity was slightly reduced upon the addition of en. Cyclic and linear nsweep voltammetry revealed that en acted as a suppressor, significantly reducing the bath’s plating rate. The Hull cell used to determine the optimum operating current density for each bath. The additive-bearing bath produced more compact deposits, better deposit grain morphology, and improved trench-filling(> 95% filling) characteristics compared to its additive-free counterpart. The enhanced super-filling characteristics acceleration (CEAC) model. SEM analysis showed thatb the deposits possessed a particulate or nodular structure, whereas EDS confirmed the presence ofNI in deposit. The Ni deposited using the bath without additives had larger particulate grains than thise using the additive-bearing bath. Higher Ni amounts were obtained in the additive-laden bath. The use the additives is a promising approach for improving the super-filling characteristics of ionic liquid plating baths.
Keywords: Nickel